SEKILAS TENTANG TAFSIR MAUDHU’I - Zuman Malaka (Sekolah Tinggi Agama Islam Taruna Surabaya, 2022)
As a holy book, the Qur'an functions as a law and a guide to the life of Muslims. In this context, Muslims in modern times often find it difficult to understand the contents of the Qur'an as a whole. Therefore, the commentators then formulate a method of understanding the Qur'an in accordance with certain themes or what is called the maudhu'i interpretation method. This article aims to discuss the meaning of maudhu'i interpretation, the history of the development of maudhu'i interpretation, steps of maudhu'i interpretation, and the advantages and disadvantages of maudhu'i interpretation. The results of the study show that maudhu'i interpretation is a method of interpretation that seeks to explain the contents of the Qur'an based on certain themes. Apart from the dynamics of its advantages and disadvantages, the maudhu'i interpretation is more in line with the living conditions of modern Muslims. The results of the study conclude that the maudhu'i interpretation method has an important role in understanding the contents of the Qur'an.